Correlation Studies and Path Analysis for Yield Enhancing Attributes in Hot Pepper - Singh, Sakshi; Joshi, A. K.; Vikram, Amit; Kansal, Sandeep; Singh, Sudha; Rajender (International Journal of Bio-resource and Stress Management, 2024)
The present study was carried out during March to September, 2018 at the Experimental Farm of the Regional Horticultural Research and Training Station (RHRST) Dhaulakuan, Dr. Yashwant Singh Parmar University of Horticulture & Forestry, Solan, HP (173230), India to investigate the interrelationship between various yield-associating factors and to construct an efficient trait for indirect selection using 21 chilli genotypes. In the study, the relationship between characteristics and path analysis showed genotypic as well as phenotypic correlation of green fruit yield plant-1 with the number of fruit plant-1, the weight of the fruit at edible maturity, and the diameter of the fruit. On the other hand, the dry matter of the fruit, the height of the plant, the number of seeds plant-1 and thousand seed weight showed a big positive correlation with red fruit yield plant-1. Path analysis at genotypic as well as phenotypic level showed maximum direct effect on number of fruit plant-1, weight of fruit at edible maturity and fruit diameter towards green yield plant-1. Conversely, fruit dry matter content, plant height and number of seeds fruit-1 and 1000 seed weight had direct effect on red fruit yield plant-1. The present outcome provided an insight that the better yield contributing genotypes might be utilized in future hot chilli improvement programme.